(untitled) (INTERFACES DA EDUCAÇÃO, 2018)
Resenha do livro: BERNARDO, Teresinha; MACIEL, Regimeire Oliveira; FIGUEIREDO, Janaína de. Racismo e educação: (des)caminhos da lei no 10.630/2003. São Paulo, Educ/Fapesp, 2017